The Motivational Factors of Participation in Wresting among Wrestlers of Different Age Groups in Kermanshah - Iraj Armand Pour; Javad Azimi Rad; Hamid Reza Negarestani (University of Tehran, 2013)
The aim of this study was to determine motivational priorities of participationin wrestling among wrestlers (Greco-Roman and freestyle) in Kermanshah city.The statistical population consisted of 4612 wrestlers of Kermanshah city. 242wrestlers in different age groups (99 adolescents, 56 juniors and 87 seniors) wereselected as a sample with random sampling method. Personal informationquestionnaire and Gale participation motivation questionnaire were used to collectdata and at the end of the training session, the questionnaires were completed.Friedman test, one-way analysis of variance and SPSS software version 13 wereused to analyze data at significance level of 0.05. Gaining success (7.44 ranking),energy depletion (6.15 ranking) and meeting friends (4.57 ranking) were the firstpriorities to participate in wrestling. There was no significant difference inmotivation of participation among different age groups (P>0.05). Results indicatedthat gaining success was the main factor of participation in wrestling inKermanshah and there was no significant difference in the priority of motivationalfactors among different age groups and those groups with various wrestlingparticipation records.